ADVANCING THE ROLE OF MUSLIM WOMEN IN THE GLOBAL ECONOMY - Tri Puji Astuti; Neyza Renindia Ritonga; Khairani Hayat Situmorang (INTERNATIONAL, Journal of Sharia Business Management, 2026)
This study aims to develop and analyze a conceptual framework for advancing the role of Muslim women in the global economy by integrating Islamic economic principles, human capital development, social capital, institutional support, and digital economy access. The research is motivated by the persistent structural, cultural, and institutional barriers that continue to limit Muslim women’s full participation in global economic activities, despite increasing access to education, entrepreneurship opportunities, and digital platforms. This study employs a qualitative approach using a systematic literature review combined with descriptive–analytical methods to synthesize relevant findings from academic journals, books, and international institutional reports. The analysis focuses on identifying key determinants, patterns, and relationships that influence Muslim women’s economic empowerment across different contexts. The findings indicate that Muslim women’s economic empowerment is a multidimensional construct shaped by the interaction of normative Islamic values, socio-economic capabilities, institutional frameworks, and technological advancement. Islamic economic principles provide the ethical foundation for participation, while human capital and social capital enhance individual capacity and access to opportunities. Institutional support plays a critical role in reducing structural barriers, and digital economy access significantly expands market participation and financial inclusion. The study further reveals that digital transformation and inclusive institutional policies are the most influential contemporary drivers of empowerment. The novelty of this research lies in its integrated conceptual model that bridges Islamic economic thought with modern development and digital economy perspectives, offering a more holistic understanding of women’s empowerment. The study provides theoretical contributions to Islamic economics and gender studies, as well as practical implications for policymakers, financial institutions, and development stakeholders in promoting inclusive and sustainable economic participation for Muslim women globally.